PENGGUNAAN PASIR SILIKA SEBAGAI BAHAN PEMBUATAN PAVING BLOCK - Mulyati, Mulyati; Fakhri Jovari, Ibrahim (ITP Press, 2024)
This research uses silica sand as a material for making paving blocks. The aim of this research is to determine the compressive strength and water absorption values of paving blocks from the use of silica sand as a partial replacement for sand in making paving blocks. The mixture for making paving blocks uses a ratio of 1 part cement and 3-part sand, with variations in the use of silica sand being 0%, 5%, 10%, 15%, and 20%. Making paving block test specimen was done manually with a mold size of 21 cm x 10.5 cm x 6 cm. Tests for compressive strength and water absorption of paving blocks were carried out at the age of 28 days. The results of research on making paving block test specimens using sand obtained an average compressive strength of 8.81 MPa and an average water absorption of 15%, using 5%, 10%, 15% and 20% silica sand were obtained, the average compressive strength is 9.56 MPa, 11 MPa, 13.5 MPa, 14.93 MPa, and the average water absorption is 13%, 10.1%,9.5%, 9.2% respectively. Thus, using silica sand as a substitute for sand in making paving blocks can increase the compressive strength and reduce the water absorption of paving block.